2005
DOI: 10.1538/expanim.54.403
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Trientine, a Copper-Chelating Agent, on Induction of DNA Strand Breaks in Kidney Cells of Long-Evans Cinnamon (LEC) Rats

Abstract: The effects of treatment with trientine, a specific copper-chelating agent, on the accumulation of copper and induction of DNA strand breaks were investigated in Long-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…400 ppm at 20 weeks of age. These results are essentially in good agreement with our previous results [8,10,11]. No significant differences were found between iron contents in the three regions of brains of WKAH and LEC rats from 4 to 26 weeks of age (Fig.…”
Section: Copper and Iron Contentssupporting
confidence: 93%
See 3 more Smart Citations
“…400 ppm at 20 weeks of age. These results are essentially in good agreement with our previous results [8,10,11]. No significant differences were found between iron contents in the three regions of brains of WKAH and LEC rats from 4 to 26 weeks of age (Fig.…”
Section: Copper and Iron Contentssupporting
confidence: 93%
“…These results show that SSBs of DNA were produced in the cerebrum and cerebellum cells of LEC rats at 24 weeks of age. Since SSBs of DNA were induced in a substantial population of LEC rat liver and kidney cells at 10 and 12 weeks of age, respectively [8,10,11], production of DNA SSBs in the brain cells occurred at a late age compared with the age at which DNA SSBs were induced in the liver and kidney cells of LEC rats. It has been reported that iron also accumulates in the liver of LEC rats and that hepatic iron may be an additional important factor contributing to liver injury in LEC rats [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Copper contents: Since it is thought that copper that has accumulated in the liver is released from severely damaged hepatocytes into the blood and deposited in other organs, including the kidney [13,27], we examined the effects of RF radiation on copper contents in the liver, kidney and serum of LEC rats (Fig. 3).…”
Section: Ast and Alt Activities In Serummentioning
confidence: 99%